NTC's practice tests for the TOEFL : test of English as a foreign language - Broukal, Milada; Nolan-Woods, Enid.; National Textbook Company (Lincolnwood, Ill. : National Textbook Co., 1997)
A practice test course that includes five complete tests in the newest format and style of the TOEFL, with realistic examples .
Keywords: English language -- Examinations -- Study guides; TOEFL